A case of mantle cell lymphoma presenting with ascites. Issue 4 (7th March 2016) - Al‐Nabulsi, Majdi; Basnet, Alina; Salerno, Vincent; Cholankeril, Michelle
Key Clinical Message: Ascites with the finding of peritoneal carcinomatosis is considered an unusual presentation for mantle cell lymphoma (MCL) and has been rarely described in literature. This case reflects the importance of cytological analysis of peritoneal fluid in a patient with intractable ascites not contributing from other comorbidities. In the event a bone marrow (BM) analysis cannot be made, this may serve as an alternative method for diagnosing MCL taking into consideration the good concordance between peritoneal fluid and BM cytological markers. Abstract : Ascites with the finding of peritoneal carcinomatosis is considered an unusual presentation for mantle cell lymphoma (MCL) and has been rarely described in literature. This case reflects the importance of cytological analysis of peritoneal fluid in a patient with intractable ascites not contributing from other comorbidities. In the event a bone marrow (BM) analysis cannot be made, this may serve as an alternative method for diagnosing MCL taking into consideration the good concordance between peritoneal fluid and BM cytological markers.